Leptin expression in placental and fetal tissues: does leptin have a functional role?. (May 2001) - Hoggard, N.; Haggarty, P.; Thomas, L.; Lea, R. G.
Abstract : Leptin is expressed in the placenta and in certain fetal tissues; however, little is known with regard to the function of this hormone in these tissues. To date, most evidence suggests that placental and/or fetal leptin acts as a fetal growth factor, but this is far from clear. Leptin may also have physiological effects on the placenta, including angiogenesis, growth and immunomodulation. The effects of placental leptin, if any, on the mother may contribute to endocrine-mediated alterations in energy balance, such as the mobilization of maternal fat, which occurs during the second half of pregnancy. In this review we will address these and other issues related to the expression of both placental and fetal leptin.